Accessibility analysis with space syntax: The pedestrian movement network in the city centre of Munich. - Schwander, Christian; Law, Stephen (My University, 2013)
We use the spatial accessibility model to assess the potential of a new retail development in the city centre. We model different scenarios of a shopping arcade and show their impact on the accessibility of the street network and on pedestrian movement potential. The analysis is not limited to the impact on the planned arcade internally, but also on the surrounding urban area. It is used to assess the different scenarios against the planning framework of the City Council and the ambitions of the developer.
Keywords: Verkehrsplanung; Stadtverkehr; Fußgängerverkehr; Verkehrsverhalten; Innenstadtverkehr; Bebauungsstruktur; Einkaufszentrum